Bioreactor scale‐down studies of suspended plant cell cultures. Issue 12 (13th October 2018) - Cheung, Caleb K. ‐L.; Leksawasdi, Noppol; Doran, Pauline M.
Abstract : The effect of dissolved oxygen fluctuations on suspended plant cells was investigated using a scale‐down stirred bioreactor system to simulate the heterogeneous conditions found in large‐scale vessels. Transgenic Nicotiana tabacum cells expressing IgG1 antibody and Thalictrum minus cells producing berberine were subjected to gas switching cycles based on a stochastic model of log‐normal circulation time distributions. Because pumping severely damaged the cells, the scale‐down approach was restricted to a single‐vessel system. Dissolved oxygen oscillations of amplitude about ±5% air saturation were achieved in the N. tabacum cultures; however, most simulations produced highly damped fluctuations due to oxygen transfer limitations and no significant effect on the cultures was observed. In contrast, berberine production by T. minus cells was reduced when fluctuations of ±10–15% air saturation were superimposed on mean dissolved oxygen tensions of 25 and 35% air saturation. This work demonstrates that dissolved oxygen gradients such as those found in large‐scale mixing vessels can be detrimental to plant cell cultures even when sufficient average dissolved oxygen levels are provided. © 2018 American Institute of Chemical Engineers AIChE J, 64: 4281–4288, 2018